Theoretical and Experimental Approach on Dielectric Properties of ZnO Nanoparticles and Polyurethane/ZnO Nanocomposites - Velayutham, T.S.; Abd Majid, Wan Haliza; Gan, W.C.; Khorsand Zak, A.; Gan, S.N. (2012)
ZnO nanoparticles (ZnO-NPs) were synthesized by a new, simple sol-gel method in gelatin media (particle size of ZnO â 30 to 60 nm). Polyurethane/ZnO nanocomposites thin films (PU/ZnO-NPs) were prepared by mixing the ZnO-NPs into PU prepolymer. The nanocomposites were structurally characterized using Fourier transmission infrared (FTIR) spectroscopy. The interaction between ZnO-NPs and PU matrix is studied by analyzing the differences in C=O region and N-H region of FTIR spectra. The morphology of ZnO and PU/ZnO nanocomposites were assessed using transmission electron micrograph, TEM, and field emission scanning electron microscope, FESEM, respectively. The dielectric properties of ZnO-NPs were attributed to the interfacial and orientation polarization. Measurement is reported for the real and imaginary parts of the ac conductivity of ZnO-NPs in the frequency range of 10 to 10 6 Hz in the temperature range 298-478 K. The experimental results are interpreted in terms of the classical correlated-barrier hopping theory. In addition, the dielectric properties of PU/ZnO nanocomposites (0-15 vol. filler concentration) were analyzed with respect to frequency. Quantitative analysis based on mixing laws for two-phase spherical dispersion system such as Lichtenecker, Maxwell, Jayasundere and Smith, and Yamada equations was used to predict the effective permittivity accurately up to 15 vol. of ZnO in PU matrix. Â© 2012 American Institute of Physics.